Desain Sistem Pengembangan Tracer Study - Alfonsa Maria Sofia Hapsari; Canakya Bima Ananda Putra (Universitas Negeri Padang, 2022)
Tracer's study is program on the situation of alumni, especially in terms of job search, work situations, and the use of competency acquisition during college. Based on the benchmarks that have been set by Dikti, the development of tracer studies can be implemented in several stages, such as system design development, data design, and interface design. With the development of the tracer study system design, it is hoped that it can become the basis for developing an integrated tracer study information system with the institution. The purpose of this discussion is to find a tracer study design that is in accordance with the rules and regulations to be applied in the institution. Using a modified Borg and Gall development model, the author focuses on product design development. The earliest design tracer studies discuss system design because this is the first stage in program design and it is the most fundamental. With this approach, designs can be developed and this is expected to be in accordance with the institutional needs and regulations of DIKTI as policymakers in higher education.